Clinical, Functional and Quality of Life Assessment of Patients with Spinal Pain Syndrome - Anna Antczak-Komoterska; Robert Ślusarz; Karolina Filipska; Anna Raszka (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
The development of civilization leads to a continuous increase in the number of diagnoses of spinal pain syndrome in patients in each age group, thus leading to the need to develop new treatment standards. Spinal pain syndromes due to the often unknown etiology cause difficult diagnosis and introduction of effective therapy. That results in difficulties in causative treatment and thus sets pain as a leading problem in the therapy. Spinal pain syndromes are a complex clinical problem that may affect the patient’s psychological and social state as well as that of their family. The result of the research carried out with the use of standardized scales in the course of the disease is the development of the patient’s nursing process. The patient’s assessment is holistic, it allows to determine the factors predisposing to the occurrence of the disease and the current state of the patient. The clinical, psychological, social as well as professional and social aspects are analyzed in a multidimensional way. The level of performing independent activities by the patient is determined by means of functional scales. Spinal pain syndromes as a global problem are also the subject of research on the quality of life of this group of patients. The essence of using these tools is the ability to correlate them with other tools. (JNNN 2017;6(4):170–173)